2020
DOI: 10.1136/jnnp-2020-322780
|View full text |Cite
|
Sign up to set email alerts
|

Early brain biomarkers of post-traumatic seizures: initial report of the multicentre epilepsy bioinformatics study for antiepileptogenic therapy (EpiBioS4Rx) prospective study

Abstract: BackgroundTraumatic brain injury (TBI) causes early seizures and is the leading cause of post-traumatic epilepsy. We prospectively assessed structural imaging biomarkers differentiating patients who develop seizures secondary to TBI from patients who do not.DesignMulticentre prospective cohort study starting in 2018. Imaging data are acquired around day 14 post-injury, detection of seizure events occurred early (within 1 week) and late (up to 90 days post-TBI).ResultsFrom a sample of 96 patients surviving mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The Epilepsy Bioinformatics Study for Antiepileptogenic Therapy (EpiBioS4Rx) and the TAPTE-(Team Approach to prevention and treatment of Post-traumatic Epilepsy) CURE grant seek to establish reliable biomarkers for PTE in animals and humans, and are anticipated to inform our working knowledge of the appearance, evaluation, and progression of biomarkers of PTE. 27 Large biomarker studies of mostly mild TBI are also nearing completion, and information from TRACK-TBI 28 (an NINDS-funded, multicenter study "Transforming Research and Clinical Knowledge in Traumatic Brain Injury") and Center-TBI 29 (a large European project that aims to improve the care for patients with Traumatic Brain Injury) will likely inform the incidence of PTE within 2 years of milder forms of TBI. Collectively, these studies have raised awareness of PTE among the general public and advocacy groups for TBI recovery.…”
Section: Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…The Epilepsy Bioinformatics Study for Antiepileptogenic Therapy (EpiBioS4Rx) and the TAPTE-(Team Approach to prevention and treatment of Post-traumatic Epilepsy) CURE grant seek to establish reliable biomarkers for PTE in animals and humans, and are anticipated to inform our working knowledge of the appearance, evaluation, and progression of biomarkers of PTE. 27 Large biomarker studies of mostly mild TBI are also nearing completion, and information from TRACK-TBI 28 (an NINDS-funded, multicenter study "Transforming Research and Clinical Knowledge in Traumatic Brain Injury") and Center-TBI 29 (a large European project that aims to improve the care for patients with Traumatic Brain Injury) will likely inform the incidence of PTE within 2 years of milder forms of TBI. Collectively, these studies have raised awareness of PTE among the general public and advocacy groups for TBI recovery.…”
Section: Biomarkersmentioning
confidence: 99%
“…However, prospective animal models have begun to identify biomarkers of specific pathways that are involved in epileptogenesis. 27 The biomarkers need to properly reflect the epileptogenesis process rather than the injury or recovery process. A large number of injury biomarkers have been proposed, including specific cellular subtypes and most of these occur during epileptogenesis.…”
Section: Biomarkersmentioning
confidence: 99%
“…They also observed cortical ribbon thinning in 46 patients. Among those, 29 remained seizure-free, 10 developed early attacks, and seven showed late seizure activity [24]. Various researchers explain the changes in the brain after injury (Table 1).…”
Section: Type Of Injury and Seizurementioning
confidence: 99%
“…In the early acute post-TBI phase (within 90 days postinjury), there is evidence showing a positive correlation between hippocampal/temporal structural abnormalities and the onset of seizure activity (11). In addition to the injury severity, the left temporal pole and left frontal cortical thinness are found to be significantly predictive factors for developing seizures after TBI (12). In addition to the cortical and subcortical structures, studies have shown that the distribution and quantification of paravscular spaces (PVSs) can be used as a potential biomarker for the development of epileptogenesis in posttraumatic epilepsy (PTE).…”
Section: Structural Mrimentioning
confidence: 99%